Como arte para desvendar-se : vieses antropológicos da experiência estética em Edith Stein - Oliveira, Renata Cabral Coutinho de (2023)
This work is an investigation on areas of connection between aesthetic experience and anthropological tendencies present in the philosophy of Edith Stein, related to the human self-formation through the activation of his spiritual dimension, as well as by the unfolding and development of the nucleus for the discovery of authenticity, and apprehension of values within the experience involving art. As a field of research, the most evident works by Edith Stein were analyzed, of all of her phases: phenomenological, anthropological, Christian and excerpts from her autobiographical writings compatible with aesthetic experiences. Also as a source of research,thematic studies published by specialists in Steinian philosophy and excerpts connected to the theme of other renowned scholars of related areas were explores. As result, it was made an analysis of the main concepts brought by the German philosopher, from the opening, through the depths of the soul, as well as the constitutives of the human being, such as feelings and empathy, focusing on the aesthetic relationship, peculiarly as to values, taking a position and updating potentialities. It also addressed the philosopher's study of the truth of art, as well as the elements of artistic experience compatible with a human formation, such as the relationship between habit and character. Finally, it was presented a possible tendency of the cultural man to return to the eternal being.